EVALUACIÓN DE ANTICUERPOS CONTRA EL VIRUS DE LA DIARREA VIRAL BOVINA DE UN HATO EN PROCESO DE ERRADICACIÓN DE LA ENFERMEDAD - Zúñiga H., Alfonso (2006)
Antibodies against bovine viral diarrhea virus (BVDV) and antigen of BVDV wereevaluated in serum samples from cattle aged 10 to 23 months (n = 148) from a dairy herdwhere the disease eradication has been carrying out since 2002. The herd is located inSanta Rita, Arequipa, Perú, and samples were collected twice on a 30-day interval.Antibodies against BVDV and BVDV antigen were analyzed by viral neutralization andcapture ELISA tests respectively. Neutralising antibodies against BVDV were detected in6.8% (10/148) of animals, and most reactors were 19 to 23 months of age. The antibodytiter ranged from 8 to >256. None persistently infected (PI) animals were found. Theincidence of infection and seroconversion in the second set of samples was nill. Theseresults suggested that the antibodies against the BVD corresponded to residual antibodiesfrom previous infections. In addition, the results indicate the BVD infection has beencontrolled.